Imports, pass-through, and the structure of retail markets - Horst Raff; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2009)
We construct a model of trade with heterogeneous retailers to examine the effects of trade liberalization on retail market structure, imports and social welfare. We are especially interested in studying the degree of pass-through of import into retail prices and the effects of retail market regulation. The paper shows that the degree of pass-through may be large when market structure effects are taken into account, and that restrictions on retailing may have significant effects on imports and the degree of pass-through. The paper helps explain the apparent discrepancy between the low observed degree of pass-through and the large benefit that consumers seem to derive from trade liberalization.
Keywords: F12; L11; 330; international trade; retailing; pass-through; firm heterogeneity; Außenhandelsliberalisierung; Außenhandelspreis; Einzelhandelspreispolitik; Marktstruktur; Wohlfahrtseffekt; Theorie